The association between Toxoplasma gondii infection and asthma in the United States: A cross-sectional survey analysis. - Heather Anholt (PLoS ONE)
The hygiene hypothesis proposes that declining exposure to microbial influences early in life is implicated in the rising trend of allergy and asthma in high-income societies. Approximately 8% of Americans have been diagnosed with asthma, representing 25 million people, and understanding how the human microbiome affects asthma could help guide exposure recommendations or microbe-based therapeutics. Toxoplasma gondii is a common gastro-intestinal microorganism that may modulate immune function. We used a cross-sectional study design to examine a public database of U.S. residents aged 6-80 years or older from the 2012-2014 survey cycles of the American National Health and Nutrition Examination Survey (NHANES) to construct an ordinal logistic regression model of the relationship between T. gondii infection and asthma. Of the 12,620 subjects tested for T. gondii infection, 89.2% were seronegative and 10.8% seropositive. No asthma was reported by 83.5% of subjects, while 16.5% reported varying degrees of asthma severity. We detected no significant association between T. gondii infection and asthma. While the unadjusted regression model suggested a small protective effect of T. gondii on asthma (OR = 0.90; 95% CI = 0.83-0.97), no effect was detected when the model was adjusted for key demographic factors (OR = 1.00, 95% CI = 0.91-1.10). While T. gondii may be a marker for the protective effect of exposure to a diversity of microbial organisms early in life, it has no apparent causal effect on asthma, or it may not be significant when considered in isolation.